Fahrenheit 451 - Bradbury, Ray, 1920-2012. (London : HarperVoyager, 2008)
In a society in which books are outlawed, Montag, a regimented fireman in charge of burning the forbidden volumes, meets a revolutionary school teacher who dares to read. Suddenly he finds himself a hunted fugitive, forced to choose not only between two women, but between personal safety and intellectual freedom.
Introduction to the 50th anniversary edition by author.
Keywords: State-sponsored terrorism -- Fiction; Totalitarianism -- Fiction; Book burning -- Fiction; Censorship -- Fiction